Risk Disclosure And Its Effect On Shareholder Returns - An Empirical Study On Malaysian Initial Public Offerings - Murugesu, John (2007)
This study is an empirical examination of the relationship between the returns of Malaysian Initial Public Offerings (IPO) companies and the risk disclosure content of the prospectus.